Kimball's prudence and two-fund separation as determinants of mutual fund performance evaluation - Wolfgang Breuer; Marc Gürtler (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2005)
We consider investors with mean-variance-skewness preferences who aim at selecting one out of F different funds and combining it optimally with the riskless asset and direct stock holdings. Direct stock holdings are either exogenously or endogenously determined. In our theoretical section, we derive and discuss several performance measures for the investor's decision problems with a central role of Kimball's (1990) prudence and of several variants of Sharpe and Treynor measures. In our empirical section, we show that the distinction between exogenous and endogenous stock holding is less important than the issue of skewness preferences. The latter are most relevant for fund rankings, when an investor's skewness preferences are not derived from cubic HARA utility so that the two-fund separation theorem is not valid. Keywords: investor specific performance measure, performance evaluation, prudence, skewness preferences
Keywords: G11; 330